Translation: A Sine Qua Non for International Confraternity - Haider, Shaharyar (Journal of Research in Humanities, 2023)
This research endeavour lays emphasis on the role of translation in creating an environment, conducive to international confraternity. It, by making a robust analysis of breaking down of cultural barears and the emergance of globalized corporatocracy, highlights the ways by which an intra-cultural as well as inter-cultural interaction can be facilitated. Moreover, it suggests various platforms: the dialogues between scholars from different cultures, a consistent communication between the source language and target language texts, i.e. which may help in ending cultural deadlocks and play their role in bringing various nations vis-a-vis. It concludes that translation is a prerequisite for inter-cultural exposure, leading to international confraternity.